Supersulfated low-molecular weight heparin synergizes with IGF1R/IR inhibitor to suppress synovial sarcoma growth and metastases. (28th February 2018) - Cassinelli, Giuliana; Dal Bo, Laura; Favini, Enrica; Cominetti, Denis; Pozzi, Sabina; Tortoreto, Monica; De Cesare, Michelandrea; Lecis, Daniele; Scanziani, Eugenio; Minoli, Lucia; Naggi, Annamaria; Vlodavsky, Israel; et al.
Abstract: Synovial sarcoma (SS) is an aggressive tumor with propensity for lung metastases which significantly impact patients' prognosis. New therapeutic approaches are needed to improve treatment outcome. Targeting the heparanase/heparan sulfate proteoglycan system by heparin derivatives which act as heparanase inhibitors/heparan sulfate mimetics is emerging as a therapeutic approach that can sensitize the tumor response to chemotherapy. We investigated the therapeutic potential of a supersulfated low molecular weight heparin (ssLMWH) in preclinical models of SS. ssLMWH showed a potent anti-heparanase activity, dose-dependently inhibited SS colony growth and cell invasion, and downregulated the activation of receptor tyrosine kinases including IGF1R and IR. The combination of ssLMWH and the IGF1R/IR inhibitor BMS754807 synergistically inhibited proliferation of cells exhibiting IGF1R hyperactivation, also abrogating cell motility and promoting apoptosis in association with PI3K/AKT pathway inhibition. The drug combination strongly enhanced the antitumor effect against the CME-1 model, as compared to single agent treatment, abrogating orthotopic tumor growth and significantly repressing spontaneous lung metastatic dissemination in treated mice. These findings provide a strong preclinical rationale for developing drug regimens combining heparanase inhibitors/HS mimetics with IGF1R antagonists for treatment of metastatic SS. Highlights: ssLMWH inhibits heparanase and activation of RTKs in synovial sarcoma cells. ssLMWH enhances IGF1R pathway inhibition and apoptosis induced by BMS754807. ssLMWH and BMS754807 synergize inhibiting growth of cells with hyperactive IGF1R. ssLMWH and BMS754807 synergize inhibiting cell migration. ssLMWH/BMS754807 cooperation results in strong antitumor/antimetastatic efficacy.